2015
DOI: 10.1371/journal.pone.0119924
|View full text |Cite
|
Sign up to set email alerts
|

γ-H2AX as a Marker for Dose Deposition in the Brain of Wistar Rats after Synchrotron Microbeam Radiation

Abstract: ObjectiveSynchrotron radiation has shown high therapeutic potential in small animal models of malignant brain tumours. However, more studies are needed to understand the radiobiological effects caused by the delivery of high doses of spatially fractionated x-rays in tissue. The purpose of this study was to explore the use of the γ-H2AX antibody as a marker for dose deposition in the brain of rats after synchrotron microbeam radiation therapy (MRT).MethodsNormal and tumour-bearing Wistar rats were exposed to 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 83 publications
1
27
0
Order By: Relevance
“…This indicates that bystander effects might play a role in low-dose radiation hypersensitivity, as observed in multiple experimental studies, such as one shown in Figure 4C (which compares curves for the LQ model and the LQ model with bystander effects). These in silico results are also confirmed with experiments by Fernandez et al 59…”
Section: Clinical Relevance Of Radiation Bystander Effectssupporting
confidence: 90%
See 2 more Smart Citations
“…This indicates that bystander effects might play a role in low-dose radiation hypersensitivity, as observed in multiple experimental studies, such as one shown in Figure 4C (which compares curves for the LQ model and the LQ model with bystander effects). These in silico results are also confirmed with experiments by Fernandez et al 59…”
Section: Clinical Relevance Of Radiation Bystander Effectssupporting
confidence: 90%
“…48,56,58 It is difficult to study these effects independently of direct effects, and, moreover, mediators and targets for bystander signals are poorly understood even after several experimental studies. 49,57,[59][60][61][62][63][64] Recently, several modeling attempts have been made to study and understand radiation bystander effects. 65,66 In one of these attempts, Powathil et al 66 used a multiscale mathematical modeling framework (Fig 2) to study the impact of radiation and radiation-induced bystander effects on both normal and tumor cells.…”
Section: Clinical Relevance Of Radiation Bystander Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…C6 glioma-bearing rats were also employed by Fernandez-Palomo et al for the study of bystander and abscopal effects when comparing MRT with BB [19]; both MRT and BB promoted radiation-induced bystander effects in the non-irradiated portion of the brain and in the bladder of the tumour-bearing animals. This same model has been used to study the dose deposition of MRT (25 µm; 200 ctc; at 35, 70 or 350 Gy peak-dose) using the marker of DNA damage γ-H2AX [44]. Moreover, the damage of the optic nerve was studied after treating the same C6 glioma in Wistar rat with cross-fired MRTs (25 µm; 200 ctc, 350 Gy peak-dose) [45].…”
Section: Gliomamentioning
confidence: 99%
“…In recent years, heavy ions radiotherapy such as high-LET carbon ion is one of the most effective treatment for cancer patients compared to conventional radiotherapy (such as X rays and  rays). By delivering higher doses to tumour volume and sparing healthy normal tissues through manipulation of the Bragg peak area, resulting in the increased therapeutic ratio, and a higher relative biological effectiveness (RBE) in cell killing and induction of DNA damage [13][14][15][16][17]. However, the underlying bystander responses and genomic instability mechanisms after high-LET carbon ions are still poorly understood and investigated.…”
Section: Introductionmentioning
confidence: 99%